(untitled) (Asian Journal of Agriculture, 2021)
Abstract. Hossain TM, Pitol MNS, Mannan MA, Khan SAKU. 2021. Impact of corm size and phosphorous on growth and floral characteristics of gladiolus (Gladiolus grandiflorus). Asian J Agric 5: 90-97. The present study was conducted to investigate the impact of corm size and phosphorus levels on the growth, flowering, corm, and cormel production of gladiolus (Gladiolus grandiflorus L.). The experiment was laid out in Randomized a Complete Block Design (RCBD) with three replications, three corm sizes, viz. S1 (31-40 g), S2 (21-30 g), S3 (10-20 g), and four phosphorus levels, viz. P0 (Control), P1 (200 kg ha-1 Triple Super Phosphate (TSP), P2 (300 kg ha-1 TSP), P3 (400 kg ha-1 TSP). The observations were recorded for various vegetative, floral, and corm parameters. Corm size significantly impacted plant height, number of leaves, number of tillers, size of the leaf, number of spikes, spike length, and number of florets. Corm size also significantly impacted all yield contributing characters and yield of corm and cormel. Large (S1) and medium-size (S2) corms were found superior to small-size (S3) corms concerning all the parameters. At 60 days after planting (DAP), the highest plant (83.53 cm), the maximum number of leaves (10.00), the utmost number of the tiller (3.00), the highest number of the spike (10.00), the largest spike (87.03 cm), the maximum number of floret (13.80), the greatest number of corm and cormel (154.67), the maximum size of corm (44.16 mm) and the highest weight (2,706.7 gm) of corm was obtained from the treatment combination of S1 (31-40 g) treated with P3 (400 kg ha-1) TSP under this observation. The obtained result will guide the farmers on what types of planting materials and how much fertilizer to use to cultivate gladiolus commercially successfully.